Analysis of Factors Affecting Farmers' Exchange Rate (NTP) in the Java Region - Gina Harlina; Unggul Heriqbaldi (Varied Knowledge Journal, 2026)
This study examines the determinants of the Farmers’ Terms of Trade (NTP) in Java, emphasizing the role of food inflation as reflected in the Consumer Price Index (CPI), the Gross Regional Domestic Product (GRDP) of the agricultural sector, and rice prices as a strategic commodity. The study employs quarterly data from 2017–2024 obtained from the Central Statistics Agency and other official sources. The Autoregressive Distributed Lag (ARDL) approach is applied to analyze both short-run and long-run relationships. The stationarity test results indicate that all variables are stationary at the first difference. The ARDL(1,1,1,1) estimation produces an R² of 0.9916, with a significant Error Correction Term (ECT) of -0.9527, confirming the presence of cointegration and a strong adjustment mechanism toward long-run equilibrium. Empirically, CPI, GRDP, and rice prices have a positive and significant impact on NTP in the long run, while their short-run effects are not statistically significant. Diagnostic tests confirm that the model is free from classical assumption problems, stable, and consistent. Causality tests reveal the dominant role of rice prices in influencing other variables. Robustness checks using the VECM approach further validate these findings, offering important policy implications.